GNSS tropospheric products at 40 ground-based GNSS stations in New Zealand (2022_01) - Li, Haobo; Wang, Xiaoming (PANGAEA, 2023)
With the rapid development of the advanced ground-based Global Navigation Satellite Systems (GNSS) tropospheric sounding technique in recent decades, it has offered unprecedented opportunities for atmospheric information acquisition. The variables obtained using this technique, e.g., zenith total delay (ZTD) and tropospheric gradients, are recognized to possess the benefits of high spatiotemporal resolution, long-term stability and all-weather capability. Therefore, in recent years, they have demonstrated their feasibility and great potential in serving the meteorology, hydrology and climate communities. In this data archive, GNSS tropospheric products at 40 ground-based GNSS stations employed in New Zealand over the period January 1-31, 2022 are provided. The whole dataset includes the site coordinates, 5-min ZTD and tropospheric gradients. Spefically, the Bernese GNSS software with the precise point positioning approach was adopted to retrieve ZTD estimates at these stations. In addition, the Vienna Mapping Function 1, the observation window of 27 h, the elevation cut-off angle of 3°, the high quality International GNSS Service Final orbits and clocks were also included in the retrieval process. To further improve the quality of the dataset, during the data processing, the phase wind-up effect, the solid Earth and ocean pole tide effects as well as relativistic delays were all modeled according to the IERS Conventions 2010.
Keywords: GNSS tropospheric sounding technique; tropospheric gradients; zenith total delay